Mycobacterial Phenolic Glycolipids Selectively Disable TRIF-Dependent TLR4 Signaling in Macrophages - Oldenburg, Reid; Mayau, Veronique; Prandi, Jacques; Arbues, Ainhoa; Astarie-Dequeker, Catherine; Guilhot, Christophe; Werts, Catherine; Winter, Nathalie; Demangel, Caroline (Frontiers in Immunology, 2018)
Phenolic glycolipids (PGLs) are cell wall components of a subset of pathogenic mycobacteria, with immunomodulatory properties. Here we show that in addition, PGLs exert anti-bactericidal activity by limiting the production of nitric oxide synthase (iNOS) in mycobacteria-infected macrophages. PGL-mediated downregulation of iNOS was complement receptor (CR)3-dependent, and comparably induced by bacterially-displayed and purified PGLs. Using Mycobacterium leprae PGL-1 as a model, we found that PGLs dampen the Toll-like receptor (TLR)4 signaling pathway, with macrophage exposure to PGLs leading to significant reduction in TIR-domain-containing adapter-inducing interferon-beta (TRIF) protein level. PGL-driven decrease in TRIF operated post-transcriptionally and independently of Src-family tyrosine kinases, lysosomal and proteasomal degradation. It resulted in the defective production of TRIF-dependent IFN-beta and CXCL10 in TLR4-stimulated macrophages, in addition to iNOS. Our results unravel a mechanism by which PGLs hijack both the bactericidal and inflammatory responses of host macrophages. Moreover, they identify TRIF as a critical node in the crosstalk between CR3 and TLR4.